Math

Aus Wiki.csoft.at

(Unterschied zwischen Versionen)
(Syntax)
(Ergebnis)
Zeile 14: Zeile 14:
:<math>a^2-b^2 = (a+b) \cdot (a-b)</math>
:<math>a^2-b^2 = (a+b) \cdot (a-b)</math>
   
   
-
:<math>V = \frac{a^3\sqrt{2}}{12} = \frac{1}{6} \cdot \begin{vmatrix} x_1 & y_1 & z_1 \\ x_2 & y_2 & z_2 \\ x_3 & y_3 & z_3 \end{vmatrix}</math>    <math>A_O = a^2\sqrt{3}</math>
+
:<math>V = \frac{a^3\sqrt{2}}{12} = \frac{1}{6} \cdot \begin{vmatrix} x_1 & y_1 & z_1 \\ x_2 & y_2 & z_2 \\ x_3 & y_3 & z_3 \end{vmatrix}</math>
:<math>\Phi= 1+\frac{1}{\Phi} = e^{\mathrm{arsinh} \frac{1}{2}} = \frac{1+\sqrt{5}}{2} = 1{,}61803398874989484820458683436564{...}</math>
:<math>\Phi= 1+\frac{1}{\Phi} = e^{\mathrm{arsinh} \frac{1}{2}} = \frac{1+\sqrt{5}}{2} = 1{,}61803398874989484820458683436564{...}</math>

Version vom 16. Juni 2006, 12:58 Uhr

Inhaltsverzeichnis

Syntax

<math>(\bar{B} + \bar{A}) \cdot (\bar{D} + \bar{C} + A)</math>
<math>a^2-b^2 = (a+b) \cdot (a-b)</math>
<math>Z(\{x[n]\}) = X(z) := \sum_{n=-\infty}^{\infty}x(n)z^{-n}</math>
<math>\Phi= 1+\frac{1}{\Phi} = e^{\mathrm{arsinh} \frac{1}{2}} = \frac{1+\sqrt{5}}{2} = 1{,}61803398874989484820458683436564{...}</math>

Ergebnis

 (\bar{B}+\bar{A})\cdot(\bar{D}+\bar{C}+A)


a^2-b^2 = (a+b) \cdot (a-b)
V = \frac{a^3\sqrt{2}}{12} = \frac{1}{6} \cdot \begin{vmatrix} x_1 & y_1 & z_1 \\ x_2 & y_2 & z_2 \\ x_3 & y_3 & z_3 \end{vmatrix}
\Phi= 1+\frac{1}{\Phi} = e^{\mathrm{arsinh} \frac{1}{2}} = \frac{1+\sqrt{5}}{2} = 1{,}61803398874989484820458683436564{...}

Siehe auch

Weblinks